Empowering Brands, Empowering Futures: A Training Program for Enhancing the Online Store of Riyaadlul Jannah Orphanage - Ariati Anomsari; Mahmud Mahmud; Sisca Dian Rahmawati; Dandy Aprilya; Nadiya Fikriyatuz Zakiyah (CV. Wira Manggala Indonesia, 2025)
The problems faced by the management of the Riyaadlul Jannah Semarang Orphanage are related to the continuity of the foster children's online business, which tends to stagnate due to a lack of understanding in gaining engagement in the market. Brand image is one of the essential elements that must be possessed by digital-era entrepreneurs in order to continue to exist in the market and not be quickly eroded by newcomers or other competitors. The solution offered in this community service is comprehensive education on creating interesting digital content on social media and training and mentoring, starting from creating social media accounts and determining the type of content to interesting captions that can form a brand image and generate positive engagement. The target output to be achieved is increasing the ability and creativity of foster children to manage digital content on social media, which will impact the formation of the online store's brand image and increase engagement. The method of community service is IbM (IPTEKS for Society), which is carried out through education and direction in two-way communication (duplex), followed by skills training and mentoring to form a brand image through interesting digital content on social media.